Inflation, nominal portfolios, and wealth redistribution in Canada - Césaire A. Meh; Yaz Terajima (Bank of Canada, 2008)
There is currently a policy debate on potential refinements to monetary policy regimes in countries with low and stable inflation such as the U.S. and Canada. For example, in Canada, a systematic review of the current inflation targeting framework is underway. An issue that has generally received relatively less attention in this debate is the redistributional effects of inflation. This omission is likely to be important since the welfare costs of inflation depend not only on aggregate effects but also on redistributional consequences. The goal of this paper is to contribute to this policy debate by assessing the redistributional effects of inflation in Canada that arise through the revaluation of nominal assets and liabilities.We find that the redistributional effects of inflation are sizeable even for low and moderate inflation episodes. The main winners are young middle-class households with substantial amounts of mortgage debt. Besides young households, inflation also represents a windfall gain for the government because of its long-term debt. Old households, rich households, and the middle-aged middle-class lose from inflation, largely due to their sizeable holdings of bonds and non-indexed defined benefit pension assets.
Keywords: D31; D58; E31; E50; 330; Monetary policy framework; Sectoral balance sheet; Inflation: costs and benefits; Inflation targets; Inflation and prices; Geldpolitik; Inflation; Verteilungswirkung; Privater Haushalt; Grundbesitz; Öffentliche Schulden; Kanada